Adaptability and yield stability of corn cultivars in the Brazilian Northeast in the agricultural year of 1998 - Carvalho, Hélio Wilson Lemos de; Leal, Maria de Lourdes da Silva; Cardoso, Milton José; Santos, Manoel Xavier dos; Carvalho, Benedito Carlos Lemos de; Tabosa, José Nildo; Lira, Marcelo Abdon; Albuquerque, Marcondes Maurício (Pesquisa Agropecuaria Brasileira, 2001)
For the agricultural year of 1998, data from a network of experiments using a randomized block design with three replications for 25 corn cultivars and 30 hybrids cultivated in nineteen and sixteen different environments, respectively, were analysed, aiming to obtain knowledge concerning to adaptability, and yield stability of cultivars in each environment. The hybrids showed an average performance 21.4% higher than the cultivars. In the experiments involving cultivars and populations, the Cargill hybrid 909 utilized as control, had a higher yield either under unfavorable or favorable environments. The yield of AL 30, BR 5028, BR 106, BR 5011, BR 5033, "Sintético Dentado", "Sintético Duro" cultivars and the CMS 50 population expressed good adaptation and yield stability under Northeastern Brazil conditions. In the experiments with hybrids, Dina 1000, Cargill 333 B, Dina 270, Braskalb XL 360, Master, AG 1051, AG 4051 and Pioneer 3041 expressed adaptation and yield stability higher than the other hybrids tested under the different environmental conditions. At favorable environmental conditions, the hybrids AG 4051 and Pioneer X 1296 B were the best ones. Even though no hybrids were specifically indicated for unfavorable environment, the recommendation of materials showing higher yields at unfavorable environments are interesting for the corn grower. This is the case of the Dina 1000, Cargill 333 B and Braskalb XL 360.